Obama's New Beginning in the Middle East - Lukacs, Nils Elias (Ergon-Verlag, 2023)
In June 2009, US president Barack Obama travelled to Cairo to seek a ‘new beginning’ in the Middle East. Beyond people’s hopes and disappointments, Nils E. Lukacs takes the Obama’s historical idea under the magnifying glass. Asking what was ‘new’, what was ‘old’, and how the ‘new beginning’ fit into its contemporary discursive context, the book demonstrates how the president’s idea introduced a paradigm shift in the history of the US-Middle Eastern relationship. In a historical perspective the author focuses the Middle East and on the region’s global interactions. He has worked extensively on the region’s relationship with the United States and the latter’s foreign policy in the region.